2023
DOI: 10.11646/phytotaxa.612.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of wood-decaying fungi in Zixishan area (Hengduan Mountains), Yunnan Province, China

XIAOJIE ZHANG,
QI YUAN,
JIANGQING SU
et al.

Abstract: Six field surveys were carried out in Zixishan area, Yunnan Province, China during 2016–2021, and 1407 specimens of wood-decaying fungi were collected. The paper summarizes the obtained results on the wood-decaying fungi of this area, consisting of 74 species belonging to 49 genera, 24 families and 7 orders. Polyporales is the dominant order (51.35% of the total species), and Hyphoderma, and Peniophorella are the dominant genera (Each accounted for 6.76% of the total) in this area. Their hosts and substrates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Recently, molecular sequences appeared to be very effective in distinguishing species of this genus, and some cryptic species have been discovered. For example, "Hydnum repandum" had been widely reported in China [8][9][10]30]; however, recent phylogenetic studies proved that the Chinese "H. repandum" is a species complex, containing at least four species, such as, H. berkeleyanum, H. melitosarx, H. orientalbidum, and H. sinorepandum. In addition, H. repandum is so far only known from Europe.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, molecular sequences appeared to be very effective in distinguishing species of this genus, and some cryptic species have been discovered. For example, "Hydnum repandum" had been widely reported in China [8][9][10]30]; however, recent phylogenetic studies proved that the Chinese "H. repandum" is a species complex, containing at least four species, such as, H. berkeleyanum, H. melitosarx, H. orientalbidum, and H. sinorepandum. In addition, H. repandum is so far only known from Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, only three species (H. repandum, H. repandum var. album, and H. rufescens) were recorded in China before 2016 [5,8,9]. Feng et al [5] conducted a molecular phylogenetic study on Hydnum in China, and the results showed that Hydnum species are very diverse in China.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…H. repandum, H. repandum var. album, and H. rufescens Pers., were reported in the country [15,20,21]. Then, Feng et al recognized 18 phylogenetic species of the genus [9].…”
Section: Introductionmentioning
confidence: 99%